Model-based risk assessment of dengue fever transmission in Xiamen City, China - Guo, Zhinan; Liu, Weikang; Liu, Xingchun; Abudunaibi, Buasiyamu; Luo, Li; Wu, Sihan; Deng, Bin; Yang, Tianlong; Huang, Jiefeng; Wu, Shenggen; Lei, Lei; Zhao, Zeyu; et al. (Frontiers in Public Health, 2023)
Background: Quantitative assessment of the risk of local transmission from imported dengue cases makes a great challenge to the development of public health in China. The purpose of this study is to observe the risk of mosquito-borne transmission in Xiamen City through ecological and insecticide resistance monitoring. Quantitative evaluation of mosquito insecticide resistance, community population and the number of imported cases affecting the transmission of dengue fever in Xiamen was carried out based on transmission dynamics model, so as to reveal the correlation between key risk factors and DF transmission. Methods: Based on the dynamics model and combined with the epidemiological characteristics of DF in Xiamen City, a transmission dynamics model was built to simulate the secondary cases caused by imported cases to evaluate the transmission risk of DF, and to explore the influence of mosquito insecticide resistance, community population and imported cases on the epidemic situation of DF in Xiamen City. Results: For the transmission model of DF, when the community population is between 10,000 and 25,000, changing the number of imported DF cases and the mortality rate of mosquitoes will have an impact on the spread of indigenous DF cases, however, changing the birth rate of mosquitoes did not gain more effect on the spread of local DF transmission. Conclusions: Through the quantitative evaluation of the model, this study determined that the mosquito resistance index has an important influence on the local transmission of dengue fever caused by imported cases in Xiamen, and the Brayton index can also affect the local transmission of the disease.